Wheat lignans and cancer prevention - Ayella, Allan K. (Kansas State University, 2007)
Wheat lignans are phenylpropane dimers linked by β-β bonds with a 1, 4-diarylbutane structure. They are biosynthesized in the cell cytoplasm through action of enzymes of the phenylpropanoid pathway. Pinoresinol lariciresinol reductase (PLR) catalyzes the final steps of biosynthesis of wheat lignans. In epidemiological and clinical investigations, studies show that high plasma lignan amounts correlate with reduced risks of breast, colon, and prostate cancers. However, in some of the studies, the results are not consistent. More consistent results are observed when animal and cell culture models are used. Our previous studies in the Wang lab demonstrated that treatment of human colon cancer cells, SW480 with lignans results in a dose and time dependent inhibition of cancer cell growth. In the first paper, we investigated direct experimental cancer preventative characteristics of a wheat lignan, secoisolariciresinol diglucoside (SDG) vs. its metabolite enterolactone in human colon cancer SW480 cells. Treatment of cancer cells with 0-40 µM SDG or enterolactone resulted into inhibition of cancer cell growth as observed by reduction of cell numbers. The reduction appeared related to induction of S-phase cell cycle arrest rather than cytotoxic effect. Further analysis revealed that SDG was more stable in cell culture medium than enterolactone. HPLC-MS/ESI showed that enterolactone is the principle metabolite in cancer cells but undetectable SDG or its metabolites were in the cells treated with SDG. In the second paper, we investigated over expression of the PLR gene and enhancement of lignan levels in transgenic wheat. We transformed wheat cultivars (‘Bobwhite’, ‘Madison’, and ‘Fielder’ respectively) with the Forsythia intermedia PLR gene under the regulatory control of the maize ubiquitin promoter. Of the total 217 transgenic wheat lines, we successfully obtained 7 transformants with the inserted ubiquitin PLR gene as screened by PCR. Real-time PCR further indicated 109-117% PLR over expression over the transgenic control in 3 transformants of the 7 at T0 generation. In addition, the levels of SDG, as determined by HPLC was found to be significantly elevated in one of the 3 positive transgenic plants. To the best of our knowledge, this is the first study reported that genetically engineered wheat with over expressed PLR enzyme enhancing phytochemical lignan has been successfully achieved.
Keywords: Wheat lignans; Cancer prevention; Genetic manipulation; Secoisolariciresinol diglucoside (SDG); Pinoresinol lariciresinol reductase (PLR); Agriculture, Food Science and Technology (0359); Agriculture, Plant Pathology (0480); Health Sciences, Nutrition (0570)